The Economics of Rising Stars - MacDonald, Glenn M. (American Economic Review, 1988)
The paper provides analysis of an occupation in which there is substantial uncertainty about individual performance, and past performance is correlated with future outcomes. In equilibrium, only the young enter the occupation and only the successful stay on. The young are numerous and earn incomes well below what their current alternative offers; success is rare and rewarded highly. The implied distribution of earnings must have positive skewness.